DECISION SUPPORT SYSTEM USING THE COMPOSITE PERFORMANCE INDEX (CPI) FOR WIRELESS REPEATER SELECTION - Joko Trianto; Mohammad Imam Shalahudin; Umbar Riyanto (Universitas Teknokrat Indonesia, 2023)
To connect to the internet, a device must have an internet connection via an internet network, one of which is through a wireless network or what is called Wireless Fidelity (Wi-Fi). On a Wi-Fi network there is a Wi-Fi router that is used to provide a connection to the internet network, but the signal from the WI-FI router is limited. Then the Wi-Fi signal needs to be strengthened with a signal booster known as a Wi-Fi Repeater or Wi-Fi Extender. Wi-Fi Repeaters are important devices for individuals, agencies and companies so that the desired areas get internet connection. So, to make a purchase of this product, foresight is needed so that the device chosen is right and in accordance with the needs. The large selection of Wi-Fi Repeater products on the market results in a person having to find information in advance regarding the specifications of the Wi-Fi Repeater product to be purchased. This has an impact on the length of the process in making decisions. The purpose of this research is to implement the Composite Performance Index (CPI) method on a decision support system for choosing Wi-Fi Repeaters, so that it can make it easier for users to determine alternatives quickly and precisely. The CPI method is used to solve decision problems with a number of alternatives through a combined index to rank alternatives from several criteria. The results of the calculations in the case study produced the highest combined index value, namely the Asus N300 Range Extender (A2) getting a score of 125, then followed by Mercusys WiFi Extender (A1) getting a score of 92.5, Comfast WiFi Extender (A3) getting a score of 100 and Xiaomi Mi AC1200 (A4) get a value of 100. The calculation results of the CPI method obtained by the system obtain the same value as manual calculations, so the developed system is declared valid. In addition, based on tests using black-box testing, it shows that the system built can function as it should.